Treatment and outcome of Philadelphia chromosome-positive acute lymphoblastic leukemia in adults after relapse. Issue 10 (2nd October 2020) - Balsat, Marie; Cacheux, Victoria; Carre, Martin; Tavernier-Tardy, Emmanuelle; Thomas, Xavier
ABSTRACT: Introduction: Despite the significant progress that has been made over the last years in the front-line treatment of Philadelphia (Ph) chromosome-positive acute lymphoblastic leukemia (ALL), relapses are frequent and their treatment remains a challenge, especially among patients with resistant BCR-ABL1 mutations. Areas covered: This manuscript reviews available data for the treatment of adult patients with relapsed/refractory Ph-positive ALL, with a focus on the role of tyrosine kinase inhibitors (TKIs), monoclonal antibodies, and immunotherapy. Expert opinion: Although a majority of patients with first relapsed Ph-positive ALL respond to subsequent salvage chemotherapy plus TKI combination, their outcomes remain poor. The main predictor of survival is the achievement of major molecular response anytime during the morphological response. More treatment strategies to improve survival are under investigation. Monoclonal antibodies and bispecific antibody constructs hold considerable promise in improving the outcomes of patients with relapsed ALL including Ph-positive ALL.